The Genetic Diversity and Antimicrobial Resistance of Pyogenic Pathogens Isolated from Porcine Lymph Nodes - Aleksandra Kaczmarkowska; Ewelina Kwiecień; Anna Didkowska; Ilona Stefańska; Magdalena Rzewuska; Krzysztof Anusz (Antibiotics, 2023)
According to the Food and Agriculture Organization of the United Nations, pork remains the most consumed meat in the world. Consequently, it is very important to ensure that it is of the highest microbiological quality. Many of the pathogens that cause lymph node lesions in pigs are zoonotic agents, and the most commonly isolated bacteria are Mycobacterium spp., Streptococcus spp., Staphylococcus aureus and Rhodococcus equi (synonymous with Prescottella equi). The prevention and treatment of zoonotic infections caused by these bacteria are mainly based on antimicrobials. However, an overuse of antimicrobials contributes to the emergence and high prevalence of antimicrobial-resistant strains, which are becoming a serious challenge in many countries. The aim of this study was to evaluate the genetic diversity and antimicrobial resistance of the Streptococcus spp. (n = 48), S. aureus (n = 5) and R. equi (n = 17) strains isolated from swine lymph nodes with and without lesions. All isolates of S. dysgalactiae, S. aureus and R. equi were subjected to PFGE analysis, which showed the genetic relatedness of the tested bacteria in the studied pig populations. Additionally, selected tetracycline and macrolide resistance genes in the streptococcal strains were also studied. The results obtained in the present study provide valuable data on the prevalence, diversity, and antimicrobial resistance of the studied bacteria. Numerous isolated bacterial Streptococcus spp. strains presented resistance to doxycycline, and almost half of them carried tetracycline resistance genes. In addition, R. equi and S. aureus bacteria presented a high level of resistance to beta-lactam antibiotics and to cefotaxime, respectively.